Analysis of Factors Affecting the Income of Micro Culinary Businesses in Denpasar City - I Wayan Danil; Ida Ayu Gde Dyastari Saskara (Digital Innovation : International Journal of Management, 2025)
This study aims to analyze the influence of business capital, product pricing, and the utilization of e-commerce on the income of micro culinary business actors in Denpasar City. The background of this research is based on the crucial role of micro enterprises in economic development, particularly in the culinary sector, which is one of the largest contributors to the Gross Regional Domestic Product (GRDP) of Denpasar City. Despite the sector's significant growth, increasing competition and uneven adoption of technology remain key challenges in improving business income. This study employs a quantitative approach with an associative research design. The population includes micro culinary business actors spread across the four districts of Denpasar City. The sample was determined proportionally using the proportionate stratified random sampling technique, and respondents were selected using accidental sampling to ensure broad representation. Primary data were collected through direct observation and structured questionnaires, while secondary data were obtained from relevant government institutions such as the Department of Cooperatives and MSMEs and the Central Statistics Agency. The data analysis technique used was multiple linear regression, supported by classical assumption tests (normality, multicollinearity, heteroscedasticity), the F-test to determine the simultaneous influence of the variables, and the t-test to analyze the partial influence of each independent variable on income. The findings indicate that simultaneously, business capital, pricing, and e-commerce significantly influence the income of micro business actors. Partially, each of these variables also shows a positive and significant effect. Business capital provides the foundation for operational activities, pricing affects consumer demand and competitiveness, while e-commerce broadens market reach and improves efficiency. These results highlight the importance of strategic financial management, appropriate pricing strategies, and the adoption of digital platforms to support income growth and sustainability of micro culinary enterprises in Denpasar City.